International Dispute Settlement - Balcerzak, Michał (International Law From A Central European Perspective, 2022)
The present chapter aims to discuss the methods and institutions designed to solve international disputes between states (and/or states and international organizations) from the perspective of the Central-Eastern European region. The chapter starts by explaining the notion of an “international dispute,” followed by a discussion of the techniques used for dispute settlement. The author invokes Article 2(3) of the UN Charter, which establishes the obligation of states to settle disputes without prejudice to international peace and security. Another important point of reference is Article 33(1) of the UN Chapter, which obliges states to seek a solution to a dispute endangering the maintenance of international peace and security, while listing a non-exhaustive list of methods used for that purpose (negotiations, enquiry, mediation, conciliation, arbitration, judicial settlement, resort to regional agencies or arrangement, or “other peaceful measures of their own choice”). In the subsequent subsections the author comments on the development of the international judiciary and the “renaissance” of arbitrage as a means of international dispute settlement, as well as the specificity of dispute resolution within European regional organizations. The last subchapter includes examples of disputes between Central and Eastern European States that have been submitted to various mechanisms of settlement since the collapse of communism in the late 1980s. KEYWORDS: international dispute settlement, peaceful resolution of disputes, international judiciary, regional European organizations